PERANCANGAN PALANG MERAH INDONESIA KOTA MUARA TEWEH - Ega Nur Muhammad Arsi; Nurfansyah Nurfansyah (ULM Press, 2024)
The Indonesian Red Cross, which is often known by the abbreviation PMI, is a national association organization located in Indonesia and engaged in the humanitarian field. The activity that was first carried out by PMI was to help victims of the Indonesian Revolutionary War of Independence and return victims of Allied and Japanese prisoners of war so that the Indonesian Red Cross has gained international recognition. The purpose of the design this time is